2014
DOI: 10.1038/nn.3682
|View full text |Cite
|
Sign up to set email alerts
|

Spine neck plasticity regulates compartmentalization of synapses

Abstract: Dendritic spines have been proposed to transform synaptic signals through chemical and electrical compartmentalization. However, the quantitative contribution of spine morphology to synapse compartmentalization and its dynamic regulation are still poorly understood.We used time-lapse superresolution STED imaging in combination with FRAP measurements, 2-photon glutamate uncaging, electrophysiology and simulations to investigate the dynamic link between nanoscale anatomy and compartmentalization in live spines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
481
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(565 citation statements)
references
References 57 publications
(95 reference statements)
54
481
7
1
Order By: Relevance
“…*p Ͻ 0.05; **p Ͻ 0.01. Oh et al, 2013). In addition, recent studies show that spine necks exert a strong influence on electrochemical compartmentalization of dendritic spines (Harnett et al, 2012;Tonnesen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…*p Ͻ 0.05; **p Ͻ 0.01. Oh et al, 2013). In addition, recent studies show that spine necks exert a strong influence on electrochemical compartmentalization of dendritic spines (Harnett et al, 2012;Tonnesen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we cannot exclude the possibility that the loss of FMRP leads to defects in the specificity of synaptic connections or affects dynamic aspects of the structure-function relationship of synapses, such as activity-dependent structural plasticity. In support of this possibility, studies have reported a change in spine turnover in Fmr1KO mice (Cruz-Martin, 2010;Pan et al, 2010).…”
Section: Normal Development Of Spine Morphologymentioning
confidence: 91%
See 1 more Smart Citation
“…Although such evidence has been essential in advancing our understanding of astroglia‐neuron communication, it leaves unresolved some critical questions regarding molecular physiology of the synaptic microenvironment, and in particular, local astroglial protrusions, on the nanoscale. Single‐molecule tracking of mGluRs and glutamate transporters in cultured astroglia has provided first glimpses on what could be the dynamic molecular micro‐organization of astrocytes (Arizono et al, 2012; Murphy‐Royal et al, 2015; Shrivastava et al, 2013), and STED imaging in organised brain tissue (Tonnesen et al, 2014) has opened up the nanoscopic world of live astroglial architecture in situ . Clearly, further implementation of super‐resolution techniques in organised brain tissue should help to bridge the knowledge gap in our understanding of the molecular micro‐physiology of astroglia and its role in information processing of brain networks.…”
Section: Discussionmentioning
confidence: 99%
“…The STED methodology has successfully been used to monitor the fine structure of dendritic spines (Bethge et al, 2013; Ding et al, 2009; Tonnesen et al, 2014, 2011), and it has recently been applied to image astroglia (Panatier et al, 2014) (Fig. 5A).…”
Section: Monitoring Of Astroglia On the Nanoscale: Emerging Techniquesmentioning
confidence: 99%